USING ILLNESS NARRATIVES AS AN EMPATHETIC CONNECTION TO REPRESENT FEMALES’ SUBJECTIVE CONSCIOUSNESS: AN ANALYSIS OF “THE YELLOW WALLPAPER" - Liao, Hung-Chang; Wang, Ya-huei (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
This study intended to use “The Yellow Wallpaper” as a case study to demonstrate how illness narratives can be used to form an empathetic connection with respect to patients’ anxiety, predicaments, trauma, or other health problems and, further, to reach self-identification and justification. To achieve the research objectives, the study used Charon’s illness narratives regarding attention → representation → affiliation and Engel, Zarconi, Pethel, et al.’s six narrative skills as a framework to examine how the nameless female narrator struggles to reach her own female identification and subjectivity in a gender-discriminated patriarchal hegemony, but gradually becomes hysterical, losing her mind, and finally, going insane.